Downward Rotation of the Capsulopalpebral Fascia, Orbital Septum, and Orbital Fat Complex: A New Technique for Lower Eyelid Rejuvenation. Issue 8 (August 2019) - Huang, Zhenying; Lee, Yongkuk; Yan, Gen; Wang, Kai
Abstract : Background: Filling of the orbitomalar sulcus through fat conservation and relocation is important for the lower eyelid rejuvenation procedure and has been reported on extensively. This study aimed to introduce a new technique—downward rotation of the capsulopalpebral fascia, septum, and fat complex in lower eyelid blepharoplasty to correct orbitomalar sulcus depression. Methods: Eighty-six patients who underwent transcutaneous lower eyelid blepharoplasty for cosmetic purposes from March 2015 to March 2016 were included in this study. The results were evaluated based on pre- and postoperative photographs, surgical records, and questionnaires. Results: The patients had no permanent or major complications. There were no fat hernia recurrences, diplopia, fat granulomas, or soft tissue irregularities. Approximately 98% of the patients were satisfied with the outcome. Conclusions: This technique more completely fills the orbitomalar sulcus and reinforces the anterior wall of the lower lid septum with capsulopalpebral fascia by rotating the orbital fat downward with the septum and capsulopalpebral fascia. Thus, it lowers the recurrence rate of the lower lid fat hernia and does not require fat removal. In particular, it has a distinct advantage in terms of the correction of the orbitomalar sulcus depression in reoperation cases, especially in patients who undergo fat removal or those with excessive fat removal.